An atlas of classification. Signage between open shelves, the Web and the catalogue - Andrea Fabbrizzi (JLIS.it, 2014)
This paper intends to present the in-progress project for the signage system of the Dewey-classified shelves in the Library of Social Sciences at the University of Florence. To make the classified arrangement effective, a signage system must clarify complexity, that is it must orient users towards the logic behind the shelf arrangement, presenting in a visible and understandable way the entities and the relationships which appear in class indexing. This signage is based on cross-media communication and integrates the library's communication means at various levels, both in the context of the same medium and between different media: between the information signs on the end-caps of the shelves, between these information signs and the library website, between the library website and the catalogue. Mobile devices such as tablets and smartphones are particularly suitable for this integrated system, because they give the possibility to access the Web while moving from shelf to shelf. The QR codes allow a link between the Dewey-classified shelves and the catalogue directly from the information signs.